CAR and TCR form individual signaling synapses and do not cross-activate, however, can co-operate in T cell activation - Barden, Markus; Holzinger, Astrid; Velas, Lukas; Mezősi-Csaplár, Marianna; Szöőr, Árpád; Vereb, György; Schütz, Gerhard J.; Hombach, Andreas A.; Abken, Hinrich (Frontiers in Immunology, 2023)
In engineered T cells the CAR is co-expressed along with the physiological TCR/CD3 complex, both utilizing the same downstream signaling machinery for T cell activation. It is unresolved whether CAR-mediated T cell activation depends on the presence of the TCR and whether CAR and TCR mutually cross-activate upon engaging their respective antigen. Here we demonstrate that the CD3ζ CAR level was independent of the TCR associated CD3ζ and could not replace CD3ζ to rescue the TCR complex in CD3ζ KO T cells. Upon activation, the CAR did not induce phosphorylation of TCR associated CD3ζ and, vice versa, TCR activation did not induce CAR CD3ζ phosphorylation. Consequently, CAR and TCR did not cross-signal to trigger T cell effector functions. On the membrane level, TCR and CAR formed separate synapses upon antigen engagement as revealed by total internal reflection fluorescence (TIRF) and fast AiryScan microscopy. Upon engaging their respective antigen, however, CAR and TCR could co-operate in triggering effector functions through combinatorial signaling allowing logic “AND” gating in target recognition. Data also imply that tonic TCR signaling can support CAR-mediated T cell activation emphasizing the potential relevance of the endogenous TCR for maintaining T cell capacities in the long-term.